Puppies - Love, Carrie; Bates, Eleanor (London Dorling Kindersley, 2017)
From a big puppy with furry ears to sleepy puppies with fluffy tummies to rub you can introduce your baby to puppies with these touch and feel textures
Picture book
1 2 13 23
Keywords: Picture book for children